Different patterns between mechanical and electrical activities: an approach to investigate gastric motility in a model of long-term diabetic rats - Marques, Rozemeire G. [UNESP]; Americo, Madileine F.; Spadella, Cesar T. [UNESP]; Cora, Luciana A.; Oliveira, Ricardo B.; Miranda, Jose Ricardo A. [UNESP] (Iop Publishing Ltd, 2014)
The relationship between time-courses of mechanical and electrical events in longstanding diabetes was investigated in rats. Magnetic markers and electrodes were surgically implanted in the gastric serosa of male rats. Simultaneous recordings were obtained by AC biosusceptometry, electromyography and electrogastrography one, three and six months after injections of saline (control) or alloxan (diabetic). Frequency and amplitude of contraction, abnormal rhythmic index and half-bandwidth were obtained (ANOVA P < 0.05). Antral hypomotility and gastric motility instability were observed in the signal waveform of diabetic rats at the three time points of study. The mean frequency (4.4 +/- 0.4 cpm) was strictly similar, but the mechanical and electrical correlation was lowest for diabetics groups. Decreases in mechanical amplitude were observed for all diabetic groups compared with control; also the ranges of frequency were much wider in diabetes. The half-bandwidth increased since the first month in mechanical recordings and only after the third month in electrical. In diabetic animals, about 40% of gastric activity was abnormal (against 12% in control) and may reach 60% in the sixth month of mechanical recordings. The multi-instrumental approach showed a more substantial deterioration in mechanical activity and created an integrative view of gastric motility for longstanding diabetic model.
Keywords: AC biosusceptometry; contractility; diabetes mellitus; electrogastrography; electromyography; hypomotility